Measurement and assessment in teaching (Pearson, 2009)
For Classroom Assessment and Test and Measurement courses in Education Departments for years, this outstanding, classic text has been the market leader for courses in Classroom Assessment and Tests and Measurement. In a presentation that assumes no previous knowledge of assessment or measurement, the text provides crystal clear step-by-step instruction on such topics as constructing test questions, aligning assessment with learning goals, and interpreting standardized tests. Providing readers with an understanding of the role of assessment in the instructional process, the book helps students learn how to construct effective test questions that are aligned with learning outcomes, evaluate published tests, and properly interpret scores of standardized tests. Measurement and Assessment in Teaching, eleventh edition, introduces the elements of measurement and assessment that are essential to good teaching, once again paving the way for future educators.